Description of a new genus and two new species of Ioninae (Isopoda: Epicaridea: Bopyridae) parasites of Leucosiidae (Decapoda: Brachyura) from Beibu Gulf - An, Jianmei M.; Yu, Haiyan; Li, Xin-Zheng (Zootaxa, 2006)
A new genus, Onkokepon n. gen., and two new species, O. articulatus n. sp. and O. beibuensis n. sp., infesting Leucosia longibranchia Shen & Chen and Leucosia unidentata de Haan, respectively, are described from Beibu Gulf in China and Vietnam. Neither of these species of Leucosia has previously been reported as bopyrid hosts. The new genus differs from other ionine bopyrid genera in the presence of a well-developed tubercular frontal lamina, a deeply digitate barbula, rudimentary subcircular pleopodal endopodites, and lacking coxal plates. O. articulatus n. sp. is distinguished from O. beibuensis n. sp. by having articulated maxillipedal palp, blunt posterolateral point of oostegite 1 and setose triangular frontal lamina of the female.